QUERy 19

#$&*

course MTH 271

04/077 pm

019. `query 19

*********************************************

Question: `q 1d 7th edition 2.6.12 2d der of -4/(t+2)^2

gWhat is the second derivative of your function and how did you get it?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First, I took the derivative of this function, which can be written separately as:

1) = (-4)/ (z^2) a.k.a. (-4)*(z^ -2) → 1’) = -4 *(-2)*(z^-3)

2) = t + 2 (aka z) → 2’) = 1

Using the chain rule, the full first derivative is:

(1’)*(2’) → (-4)[(-2)*(1)*(t + 2)^-3] → (-4)*(-2)*(t + 2)^-3 → 8(t + 2)^-3 a.k.a. 8/ (t+2)^3

This is only the first derivative, to find the second derivative, the derivative of this function must be found:

f’(t) = 8/ (t + 2) ^3 → f’’(t) = 8 * (-3) * (t + 2)^ -4 → -24/ (t + 2) ^4

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`a You need to use the Constant Rule. [ -4(t+2)^-2 ] ' = -4 [ (t+2)^-2 ] '

By the chain rule, with g(z) = z^-2 and h(t) = t + 1 this gives us -4 [ h '(t) * g ' ( h(t) ] =

-4 [ (t+2) ' * -2(t+2)^-3 ] = -8 ( t+2)^-3.

So g ' (t) = -8 ( t+2)^-3.

Using the same procedure on g ' (t) we obtain

g '' (t) = 24 ( t + 2)^-4. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): OK

------------------------------------------------

Self-critique Rating: 3

*********************************************

Question: `q 3d 7th edition 2.6.28 2.6.28 f'''' if f'''=2`sqrt(x-1)

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

f’’’’ is the derivative of f’’’:

2 * (x - 1)^1/2 → 2 * (1/2) * ( x - 1)^-1/2

→ 1/ 2(sqrt(x - 1))

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`a The fourth derivative f '''' is equal to the derivative of the third derivative. So we have

f '''' = (f ''') ' = [ 2 sqrt(x-1) ] ' = 2 [ sqrt(x-1) ] '.

Using the Chain Rule (noting that our function is sqrt(z) with z = x - 1, and that sqrt(z) ' = 1 / (2 sqrt(z) ) we get

2 [ (x-1)' * 1/(2 sqrt(x-1) ) ] = 2 [ 1 * 1/(2 sqrt(x-1) ) ] = 1 / sqrt(x-1). **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): OK

------------------------------------------------

Self-critique Rating: 3

*********************************************

Question: `q 5 7th edition 2.6.43 (was 2.6.40) brick from 1250 ft

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

Assuming that a = -32, from a previous problem,

Acceleration = s’’(t) = V’ = -32

Velocity = s’(t) = -32t + b

Position = s(t) = -16t^2 + bt + c

-

When t = 0, s(0) = -16(0)^2 +b(0) + c → When t = 0, position is 1250, so c = 1250

Also, when t = 0, s’(0) = -32(0) + b → b = 0

So the position function is s(t) = -16t^2 + 1250

When the ball hits the sidewalk, acceleration hits 0 so:

0 = -16t^2 + 1250 → -16t^2 = -1250 → t^2 = 1250/16 → t = +- sqrt(1250/16) →

t = +- 8.84 so when the ball hits the sidewalk, at acceleration = 0, time = 8.84 seconds.

v(t) = -32t + b → v(8.84) = -32(8.84) → -282.88 ft/sec

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`a The detailed analysis is as follows:

-The equation comes from a = -32; since a = v' we have v' = -32 so that v = -32 t + c. Then s' = v so s' = -32 t + c and s = -16 t^2 + c t + k. c and k are constants.

If s(t) = -16 t^2 + c t + k and at t = 0 we have s = 1250, then

s(0) = -16 * 0^2 + c * 0 + k so k = 1250 and s(t) = -16 t^2 + c t + 1250.

If the ball is dropped from rest then the initial velocity is v(0) = 0 so

v(0) = -32 t + c = 0 and -32 * 0 + c = 0 so c = 0.

So s(t) = -16 t^2 + c t + k becomes s(t) = -16 t^2 + 1250.

To find how long it takes to hit the sidewalk:

Position function, which gives altitude, is y = -16 t^2 + 1250.

When the brick hits the sidewalk its altitude is zero.

So -16 t^2 + 1250 = 0, and t = + - `sqrt(1250 / 16) = + - 8.8, approx.

The negative value makes no sense, so t = 8.8 seconds.

To find how fast the brick was moving when it hit the sidewalk:

velocity = -32 t so when t = 8.8 we have velocity = -32 * 8.8 = -280 approx.

That is, when t = 8.8 sec, v = -280 ft/sec. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): OK

------------------------------------------------

Self-critique Rating: 3

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

#*&!

&#This looks good. Let me know if you have any questions. &#